Differential coassembly of α1-GABAARs associated with epileptic encephalopathy - Hannan, Saad (2021)
GABAA receptors (GABAARs) are profoundly important for controlling neuronal excitability. Spontaneous and familial mutations to these receptors feature prominently in excitability disorders and neurodevelopmental deficits following disruption to GABA-mediated inhibition. Recent genotyping of an individual with severe epilepsy and Williams-Beuren syndrome identified a frameshifting de novo variant in a major GABAAR gene, GABRA1. This truncated the α1 subunit between the third and fourth transmembrane domains and introduced 24 new residues forming the mature protein, α1Lys374Serfs*25. Cell surface expression of mutant murine GABAARs is severely impaired compared with WT, due to retention in the endoplasmic reticulum. Mutant receptors were differentially coexpressed with β3, but not with β2, subunits in mammalian cells. Reduced surface expression was reflected by smaller IPSCs, which may underlie the induction of seizures. The mutant does not have a dominant-negative effect on native neuronal GABAAR expression since GABA current density was unaffected in hippocampal neurons, although mutant receptors exhibited limited GABA sensitivity. To date, the underlying mechanism is unique for epileptogenic variants and involves differential β subunit expression of GABAAR populations, which profoundly affected receptor function and synaptic inhibition.